Impact of Transgenic Maize Ruifeng125 on Diversity and Dynamics of Bacterial Community in Rhizosphere Soil - Chaofeng Hao; Xinyao Xia; Chao Xu; Hongwei Sun; Fan Li; Shuke Yang; Xiaohui Xu; Xingbo Lu (Microorganisms)
With the development of commercialized planting of genetically modified crops, their ecological security risks remain a key topic of public concern. Insect-resistant genetically modified maize, Ruifeng125, which expresses a fusion Bt protein (Cry1Ab-Cry2Aj), has obtained the application safety certificate issued by the Chinese government. To determine the effects of Ruifeng125 on the diversity and dynamics of bacterial communities, the accumulation and degradation pattern of the fusion Bt protein in the rhizosphere soil of transgenic maize were detected. Results showed that the contents of Bt protein varied significantly at different developmental stages, but after straw was returned to the field, over 97% of Bt proteins were degraded quickly at the early stages (≤10 d) and then they were degraded at a relatively slow rate. In addition, the variations in bacterial community diversity in the rhizosphere soil were detected by 16S ribosomal RNA (Rrna) high-throughput sequencing technology. A total of 44 phyla, 435 families, and 842 genera were obtained by 16S rRNA sequencing, among which Proteobacteria, Actinobacia, Acidobacter Acidobacterium, and Chloroflexi were the dominant taxa. At the same developmental stage, no significant differences in soil bacterial diversity were detected between Ruifeng125 and its non-transgenic control variety. Further analysis revealed that developmental stage, rather than the transgenic event, made the greatest contribution to the changes in soil microbial diversity. This research provides important information for evaluating the impacts of Bt crops on the soil microbiome and establishes a theoretical foundation for their environmental safety assessment.